Innovative pedagogical technologies while teaching discipline «Foreign Language for Professional Purposes» in Ukrainian institutions of higher medical education. - Kulichenko, A. K.; Куліченко, Алла Костянтинівна (My University, 2022)
Rapid changes in modern society require technologies to differentiate medical education, which help educational institutions and are appropriate in certain educational situations or should be abandoned. Thus, according to J. Moran and coauthors, «continuous innovation between medical education and students remains organizations to make full use of the potential of pedagogical technologies» [8, p. 796].
Keywords: тези доповідей